2019
DOI: 10.2147/jpr.s220201
|View full text |Cite
|
Sign up to set email alerts
|

<p>Electroacupuncture Alleviates Spared Nerve Injury-Induced Neuropathic Pain And Modulates HMGB1/NF-κB Signaling Pathway In The Spinal Cord</p>

Abstract: BackgroundNeuropathic pain with complications greatly affects patients worldwide. High mobility group box 1 (HMGB1) has been shown to contribute to the pathogenesis of neuropathic pain; thus, suppression of HMGB1 may provide a novel therapeutic option for neuropathic pain. Electroacupuncture (EA) has been indicated to be effective in attenuating neuropathic pain, but the underlying mechanism remains to be fully clarified. We aim to explore whether 2Hz EA stimulation regulates the spinal HMGB1/NF-κB signaling i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 42 publications
(70 reference statements)
2
25
0
Order By: Relevance
“…In addition, HMGB1 could promote the production of proinflammatory cytokines by regulating TLR2 or TLR4, causing the activation of coagulation and microvascular thrombosis [48]. Moreover, HMGB1/NF-κB signaling has been widely reported in inflammation-associated acute injuries, including spared nerve injury [49], acute lung injury [50] and cerebral ischemia-reperfusion injury [51]. We demonstrated that miR-22-3p overexpression reduced the expression of p-65 and TLR4, accompanied by the inhibition of HMGB1, suggesting that miR-22-3p may reduce inflammatory response and apoptosis, in sepsis-induced kidney injury rat model and LPS induced cell injury model, through HMGB1/NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HMGB1 could promote the production of proinflammatory cytokines by regulating TLR2 or TLR4, causing the activation of coagulation and microvascular thrombosis [48]. Moreover, HMGB1/NF-κB signaling has been widely reported in inflammation-associated acute injuries, including spared nerve injury [49], acute lung injury [50] and cerebral ischemia-reperfusion injury [51]. We demonstrated that miR-22-3p overexpression reduced the expression of p-65 and TLR4, accompanied by the inhibition of HMGB1, suggesting that miR-22-3p may reduce inflammatory response and apoptosis, in sepsis-induced kidney injury rat model and LPS induced cell injury model, through HMGB1/NF-κB pathway.…”
Section: Discussionmentioning
confidence: 99%
“…It is well known that EA stimulation served as an subsidiary therapy has been widely used to relieve neuropathic pain with fewer side effects [ 22 , 29 ]. Experiments demonstrated that EA stimulation has an inhibitory effect on mechanical hypersensitivity in spinal nerve ligation (SNL) rats [ 9 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Stimulation with 2 Hz EA alleviates SNL-induced neuropathic pain by promoting the occurrence of long-term depression (LTD) in the spinal dorsal horn [ 27 ]. Our previous studies have demonstrated that 2 Hz EA successfully ameliorated mechanical hypersensitivity through blockade of microglial activation and pro-inflammatory cytokine IL-1β production in the spinal cord of SNI rats [ 23 , 28 , 29 ], but the underlying mechanisms remain largely unknown. Based on the fact that neuroinflammatory response is regarded as a crucial role in the pathogenesis of neuropathic pain, including the alterations of pain-related signaling molecules [ 30 , 31 ], BDNF is known to be an endogenous neuromodulator in the nociceptive pathway and exerts a critical action via its interactions with TrκB receptor [ 8 ], and the BDNF/TrκB signaling pathway plays an important role in central sensitization and neuropathic pain development.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence revealed that the inhibitory effect of EA stimulation is highly related to the modulation of neuroinflammation [17][18][19]. Our recent study demonstrated that 2 Hz EA alleviated SNIinduced neuropathic pain through blockade of microglial activation and proinflammatory cytokine IL-1β release in the spinal cord [20,21]. Other study also reported that CX3CR1 knockout mice exhibit the reduction of inflammatory and neuropathic pain and a decrease of spinal microglial response [22].…”
Section: Introductionmentioning
confidence: 77%
“…2 Hz EA treatment of SNI rats was conducted as previously described [20,21]. Briefly, rat was housed using a specially designed holder with its both hind legs and tail exposed; the skin of hind legs in the rat was sterilized using 75% alcohol.…”
Section: Electroacupuncture Stimulationmentioning
confidence: 99%